Autism spectrum disorders in adolescents and adults : evidence-based and promising interventions - Tincani, Matt.; Bondy, Andy. (New York : The Guilford Press, 2014)
"We've edited this collection of chapters on evidence-based and promising practices for adults with ASD. During the past 25 years or so there has been a concomitant increase in research and publications regarding the identification, assessment, and education of these children. This heavy focus on children is understandable given the promise of early identification and intervention. However, there remains a paucity of research and guidelines that focus on the issues that face adults with ASD. We asked a number of the leading researchers to write chapters on critical issues related to the well-being of adults with ASD. Each set of authors was asked to review the current literature associated with a wide array of topics. In addition to reviewing key research, each chapter provides some examples of how specific features and strategies may influence a hypothetical case in terms of practical decision making."--
I. Introduction. Characteristics of adults with high-functioning autism spectrum disorders / Brenda Smith Myles, Amy Bixler Coffin, Donna J. Owens, and Courtney Yantes -- Autism spectrum disorders and the family / Lauren Pepa and Sandra L. Harris --II. Transitioning from adolescence to adulthood. Effective secondary education and transition for adolescents with autism spectrum disorders / Michael L. Wehmeyer and Dianne Zager -- Postsecondary education for students with autism spectrum disorders / Jane Thierfeld Brown, Lorraine E. Wolf, and Christine Wenzel -- III. Instructional and behavioral interventions to promote quality of life. Behavioral interventions for complex communication and social skills in adults with autism spectrum disorders / Angelica Aguirre, John O-Neill, Ruth Anne Rehfeldt, and Valerie Boyer -- Teaching functional communication to adults with autism spectrum disorders / Russell Lang, Jeff Sigafoos, Larah van der Meer, Amarie Carnett, Vanessa A. Green, Giulio E. Lancioni, and Mark F. O'Reilly -- Positive behavior support for adults with autism spectrum disorders / Matt Tincani and Shannon Crozier -- Skill-building interventions for adolescents and adults with autism spectrum disorders / Peter F. Gerhardt, Maria Fernanda Garcia, and Anthony Foglia -- Sexuality and relationships for individuals with autism spectrum disorders / Jason C. Travers and Peggy Schaefer Whitby -- Toward a balanced leisure lifestyle for adults with autism spectrum disorders / Phyllis Coyne and Ann Fullerton --IV. Employment, independence, aging, and policy. Meaningful employment for individuals with autism spectrum disorders / Paul Wehman, Pamela Sherron Targett, Carol Schall, and Staci Carr -- Facilitating successful independent living skills for adults with high-functioning autism spectrum disorders / Brenda Smith Myles, Daniel Steere, Cathy Pratt, Ruth Aspy, Barry G. Grossman, and Shawn A. Henry -- Aging, estate planning, and funding services for adults with autism spectrum disorders / Carol Markowitz -- Legal issues and autism spectrum disorders / Beverly L. Frantz and David W. Zellis.
Includes bibliographical references and index.
Keywords: Autism spectrum disorders in children -- Treatment; Autism spectrum disorders -- Treatment; PSYCHOLOGY / Psychopathology / Autism Spectrum Disorders; MEDICAL / Psychiatry / General; EDUCATION / Special Education / Social Disabilities; SOCIAL SCIENCE / Social Work; PSYCHOLOGY / Psychotherapy / Counseling